2004
DOI: 10.1117/12.556659
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-resistant polymer-based photonics for space applications

Abstract: Empirical data regarding the radiation induced responses of Mach Zehnder interferometric electro-optic polymer based modulators (PBMs) operating at 1310 and 1 550 nm and broadband InP quantum dot (QD) polymer photodetectors (PPDs) operating into the near infrared (NIR) are reported. Modulators composed of spun-on materials and hybrid electostatically self assembled (ESA) and spun-on NLO materials are examined for changes to their half-wave voltage and insertion losses following a gamma-ray total dose of 163 kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
0
7
1
Order By: Relevance
“…The control sample was located in proximity to the irradiation area, not irradiated, but This behavior is contrary to that expected or reported for most NLO EO polymer thin film devices [7,8,10,11,14]. Previous studies have shown that operation of similar CLD-1 devices under inert gas environments have remained stable in operation while CLD-1 devices operated under normal atmospheric conditions deteriorate with time [14].…”
Section: Responses Of Irradiated Afrl/sndp Pbmscontrasting
confidence: 40%
See 1 more Smart Citation
“…The control sample was located in proximity to the irradiation area, not irradiated, but This behavior is contrary to that expected or reported for most NLO EO polymer thin film devices [7,8,10,11,14]. Previous studies have shown that operation of similar CLD-1 devices under inert gas environments have remained stable in operation while CLD-1 devices operated under normal atmospheric conditions deteriorate with time [14].…”
Section: Responses Of Irradiated Afrl/sndp Pbmscontrasting
confidence: 40%
“…By including the high dose loss data of SNDP Sample Set 3, the gamma-ray degradation rates in Figure 34 were reduced compared to the waveguide degradation rates derived at lower dose and previously shown in Figure 15. Reduction to the 4 and 6 µm degradation rates were 14.5% and 15.6 % relative to those shown in Figure 35 shows the paired PBM data of SNDP Sample Set 2 in Table 4 combined with the averaged response data of Sample set 3 (shown in Table 5 PBM device a showed strong indication of ∆V π beginning to saturate after receiving a mixed gamma-ray and proton total dose of 209 krad(Si) [22].…”
Section: Data Fusionmentioning
confidence: 97%
“…Degradation was especially pronounced in liquid PPDs where the data suggested that prolonged relaxation times following pulsed photo-illumination may have resulted from charge trapping and a reduction in the effective conductivity of the charge transport material [1,2]. However, the radiation induced reduction in the output photovoltage for the NanoSonic fabricated Ru(N3) devices appeared to saturate between 51-100 krad(Si) suggesting that the Ru(N3)-devices were potentially resistant to ionizing radiation at higher dose [1,2]. By incorporating appropriate size InP QDs into the polymer matrix, a shift of the PPD wavelength response towards the near-IR (800 -1000 nm) was predicted.…”
Section: Introductionmentioning
confidence: 99%
“…However, sufficient absorption occurred in the near-IR allowing study of the radiation -induced effects over the entire InP QD PPD spectral response range (~ 400-1000 nm). As recently reported, irradiating photovoltaic PPDs using gamma-ray and protons radiation early in material or device development stage provides an early quantitative measure of the PPD response to ionizing and nuclear particle induced displacement effects [1,2]. Quite often promising photonic materials and devices are developed at great expense and later found to be lacking in their ability to resist or survive in radiation environments.…”
Section: Tuning the Optical Absorption Of Inp Qds To The Near-irmentioning
confidence: 99%
“…Of special interest are recent studies conducted and reported by Taylor and colleagues [8][9][10][11][12] regarding radiationinduced effects and hardening of non-linear optical (NLO) polymer based modulators. While commercial polymer modulators are emerging, only a modicum of data has been reported for gauging the eventual space qualification of these devices.…”
Section: Introductionmentioning
confidence: 99%